TEACHING COST ACCOUNTING. - Lawrence, W. B. (The Accounting Review, 1933)
Abstract The article focuses on different aspects of teaching cost accounting. Commerce students who have had little or no business experience present a problem to instructors in cost accounting because their lack of background keeps them from comprehending the aims sought by a cost system and particularly the managerial aspects of such a system. This condition seems to be general with all classes of students, whether they be those in day classes who are taking a complete commerce course or evening students who have some experience in business and are seeking to develop themselves in a special branch of accountancy. It therefore seems necessary for the instructor in cost accounting to carry on some preliminary work with his students to give them a philosophy of cost accounting whereby they will appreciate the importance of internal transactions in a business, the use that can be made of cost records for managerial purposes as apart from mere record keeping and the general relation that exists between all the manifold activities of a business, as well as some idea of what those activities are.